Investigation the effects of cigarette smoke on immunoglobulin levels in serum and saliva samples of smoker and non-Smoker subjects using antibody-microarray technology - Tarbiah, Nesrin (2017)
Cigarette smoke (CS) has many damaging effects on the body, and the chronic inhalation of cigarette smoke can change immunological functions through impact on both innate and adaptive immunity. The incidences of many diseases are affected by the adverse effects of cigarette smoke on the immune system, and the induction of an inflammatory response, which affects several tissues and organs. On this basis, a comparison of smokers′ and non-smokers′ immunoglobulin levels could provide valuable insights into the mechanisms of smoking related diseases. Although the effects of cigarette smoking on humoral and cellular immunity have been investigated previously, the results have varied between the studies, and therefore more research is still required.